DAMPAK KELAPA SAWIT DALAM PEMBANGUNAN BERKELANJUTAN : ANALISIS KEBIJAKAN PUBLIK DI INDONESIA - Rani, Nur (Universitas Djuanda, 2025)
Green economy focuses on sustainable development while considering environmental preservation at local, regional, and global levels. This approach supports sustainable economic growth by taking environmental impacts into account, creating job opportunities, and utilizing renewable energy to enhance societal well-being. In Indonesia, the agriculture, plantation, and fisheries sectors contribute 30.32% to GDP and employ 16.2 million workers, with palm oil being one of the main commodities. This study aims to analyze the impact of palm oil on sustainable development from a public policy perspective. Using a qualitative research method based on a literature review, this study examines the role of palm oil within the context of the problem stream, policy stream, and politics stream. The findings indicate that the problem stream includes environmental issues such as deforestation, water pollution, and wildlife population decline, as well as social issues such as land conflicts and community dependence on the palm oil industry, and economic challenges such as financial losses due to European Union policies. The policy stream involves programs such as the B30 biodiesel initiative and ISPO certification, while the politics stream encompasses international pressure, domestic policies, and government commitments to sustainable development through restrictions on new land permits. The novelty of this research lies in its comprehensive analysis of the integration of the three policy streams in assessing the impact of palm oil, providing insights for strengthening green economy-based policies to support environmental sustainability and societal welfare. Better policies are needed in palm oil management, including improved inter-agency coordination, transparency, and community engagement to promote economic, social, and environmental sustainability.